2009
DOI: 10.3797/scipharm.0906-08
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of some Xanthone Derivatives on the Activity of J-774A.1 Cells

Abstract: The chemiluminescence of stimulated cells with phorbol myristate acetate and the production of nitric oxide after stimulation with lipopolisaccharide in the presence of the parent compounds FAA (flavone-8-acetic acid = (4-oxo-2-phenyl-4H-chromen-8-yl)acetic acid), XAA (xanthone-4-acetic acid = (9-oxo-9H-xanthen-4-yl)acetic acid), and appropriate xanthone derivatives (1-7) was determined. Also the toxicity of the FAA, MFAA ((6-methyl-4-oxo-2-aryl-4H-chromen-8-yl)acetic acid), XAA and 1-7 against J-774A.1 cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Marona et al reported the synthesis [ 138 ] of three new chiral analogues of XAA 160 – 162 ( Figure 15 ) and the evaluation of their cytotoxicity against J7774A.1 cells [ 139 ]. Compounds 160 and 161 were obtained by condensation of 2-hydroxyxanthone and 2-methyl-6-hydroxyxanthone, respectively, with α-bromopropionic acid and compound 162 by esterification of compound 161 [ 138 ].…”
Section: Synthetic Chiral Derivatives Of Xanthonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Marona et al reported the synthesis [ 138 ] of three new chiral analogues of XAA 160 – 162 ( Figure 15 ) and the evaluation of their cytotoxicity against J7774A.1 cells [ 139 ]. Compounds 160 and 161 were obtained by condensation of 2-hydroxyxanthone and 2-methyl-6-hydroxyxanthone, respectively, with α-bromopropionic acid and compound 162 by esterification of compound 161 [ 138 ].…”
Section: Synthetic Chiral Derivatives Of Xanthonesmentioning
confidence: 99%
“…Compounds 160 and 161 were obtained by condensation of 2-hydroxyxanthone and 2-methyl-6-hydroxyxanthone, respectively, with α-bromopropionic acid and compound 162 by esterification of compound 161 [ 138 ]. Regarding the biological activity tested, it was found that all CDXs showed weak cytotoxicity [ 139 ].…”
Section: Synthetic Chiral Derivatives Of Xanthonesmentioning
confidence: 99%
“…Compound 147 was able to bind specifically to cellular proteins through photoreaction, which could be a useful tool to identify the receptors of DMXAA ( 2 ) [148]. In 2009, Marona et al reported the synthesis of seven new analogues ( 155 – 161 ) (Figure 11) of DMXAA ( 2 ), with weak cytotoxicity against J7774A.1 cells [149].…”
Section: Synthetic Carboxyxanthone Derivativesmentioning
confidence: 99%